A brief overview of the impact of avian influenza on animals - Hancock, John T; Rouse, Ros C; Robinson, Gareth; Craig, Tim J (Animal Review, 2025)
Avian influenza (AI) virus, and the (HPAI)H5N1 subtype in particular, is a serious problem for many wild bird populations, where devastating losses have been reported. However, AI is not restricted to bird species. Here, a literature search was used to assess the range of animals infected by AI. This included reports in the scientific journals as well as news outlets. As can be seen, infection has been reported in commercial mammals such as cattle and mink where there is close animal-to-animal contact, as well as close contact with humans. Some domestic animals, such as cats, have been reported to be AI virus positive too, again where there is a possibility that conditions will be conducive to animal-to-human transmission. Many animals in the wild have been found to be infected with AI virus, and many of these, perhaps not surprisingly, are marine mammals. Mink-to-mink viral transmission has been suggested to have taken place, but most animals which have been infected have had close contact with birds, often handling or eating carcasses. There are also reports of humans becoming infected, for example, from cattle. Although this overview is intended to be neither comprehensive nor quantitative it is hoped that such information will aid in the management of AI, especially (HPAI)H5N1, in the future.